Poly-skilling and advanced practice roles in perioperative care: protocol for a realist synthesis of evidence - David Walker; Ann Griffin; Carolina Britton; Della Freeth (BMJ Open)
Introduction An ageing population and a workforce crisis have triggered an ambitious UK strategy for sustained delivery of healthcare. In perioperative care (the management of patients from contemplation of surgery until full recovery), it is recognised that interventions are needed to place the workforce on a more sustainable footing through cross-functionality and skill-shifting, namely with advanced practice roles. However, despite some reports and reviews in the literature, it is unclear how skills development efforts may potentially support workforce transformation for an effective and resilient perioperative care workforce. Thus, drawing causal inferences for policy-making that is both evidence based and rooted in theory is challenging. A scoping review, reported within this protocol, confirmed that ‘poly-skilling’ and ‘advanced practice roles’ are critical to this workforce transformation, but the mechanisms through which interventions in this area may work are not understood. A synthesis of evidence is, therefore, proposed in this protocol, to understand what works for whom and under what circumstances, in relation to poly-skilling and advanced practice roles in workforce transformation for sustained healthcare delivery.Methods and analysis This protocol sets out the plan to undertake a realist synthesis of the related literature, with theory elicitation (step 1), search for empirical evidence (step 2), selection and appraisal of evidence (step 3) and programme theory refinement (step 4). Exploratory reviews of the literature and key informants’ inputs will produce initial hypotheses as to what it is about interventions in poly-skilling and advanced practice roles that work and why. Data from the literature will then be collected based on relevance, rigour and richness. The iterative analysis and synthesis of these data will produce causal links between contexts, mechanisms and outcomes. The results will inform a realist evaluation, to be undertaken as part of doctoral research, to better understand the mechanisms that support workforce transformation through poly-skilling and advanced practice roles.Ethics and dissemination As a review of previously published literature, the evidence synthesis proposed in this protocol does not require formal ethical approval. Recommended ethical considerations regarding the involvement of key informants, who are not study participants but a consultative group, are presented in this protocol. A formal ethics approval will be sought ahead of the later empirical stage of the research. The results of the realist synthesis proposed in this protocol will be fed back to the local National Health Service organisation and Integrated Care Board and disseminated to the research community via presentations at conferences and a peer-reviewed journal article.PROSPERO registration number CRD42024512164.